A frustrated phase driven by competition among layer structures. Issue 30 (3rd July 2017) - Sasaki, Takashi; Takanishi, Yoichi; Yamamoto, Jun; Yoshizawa, Atsushi
Abstract : Competition among the three different layer structures produces the frustrated phase with spatiotemporal fluctuations of the molecules. Abstract : Using our designed ternary system consisting of a semiperfluorinated smectic liquid crystal and two nematic liquid crystals, we investigated their phase transition behaviour using polarizing optical microscopy, differential scanning calorimetry and X-ray diffraction. A mixture containing 20 mol% of the semiperfluorinated compound was found to exhibit the following unusual phase sequence: isotropic liquid − isotropic liquid + smectic A phase − nematic phase − unidentified frustrated phase (X) − modulated phase (Y) − modulated phase (Z). The frustrated phase showed a fan-shaped texture characteristic of a smectic phase, but no peak corresponding to the layer spacing was detected. No difference was found in the shearing stress between the high-temperature N phase and the frustrated phase, but electro-optical switching observed in the N phase was not detected in the frustrated phase. We discuss how the molecules organize the unusual phase transition behaviour.